Compensation Analysis in Improving Employee Performance at Bank Muamalat, Baturaja City - Dedi Siswanto; Nurma Nirmala; Sayu Mainingsih (LP2M IAIN Palopo, 2025)
This study examines the employee compensation system at Bank Muamalat in Baturaja City using a descriptive qualitative approach, combining a socio-historical perspective and Islamic values ​​in compensation practices in Islamic banking. The compensation analyzed includes direct compensation (salary and incentives) and indirect compensation (allowances, facilities, and Umrah pilgrimage). The results show that a fair, timely, and Islamically sound compensation system contributes significantly to improving employee motivation, well-being, and performance. Comprehensive and transparent performance assessments also support rational and accountable compensation. These findings reinforce the importance of integrating moral and religious values ​​in Islamic banking human resource management to achieve high productivity and loyalty.